Determination of changes in the nutrition and physical activity status of academicians during the pandemic period - Akbay, Gulsen Delikanli; Karakullukcu, Erdinc (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the changes in nutrition habits, physical activity levels, sedentary behaviours, sleep patterns and quality of academicians before and during the coronavirus disease-2019 pandemic. Method: The descriptive, cross-sectional study was conducted from January to September 2022 after approval from Karadeniz Technical University, Turkiye, and comprised academicians working at public universities in Turkiye during the coronavirus disease-2019 pandemic period. The survey questionnaire was distributed online to all public universities across the country. The participants’ food consumption before and during the epidemic, sleep patterns and physical activity conditions were assessed. Data was analysed using SPSS 22. Results: Of the 299 academicians,166(55.5%) were female and 133(45.5%) were male. Overall age range was 19-65 years, with 122(40.8%) subjects aged 35-44 years. A significant number of academicians 143(47.83%) reported changes in their eating habits, while even more 189(64.29%) indicated that a sedentary lifestyle had a negative impact on their health. There was a significant increase in the number of snacks (p<0.001). A total of 125(42.09%) participants reported using nutritional supplements during the pandemic, with vitamins, multivitamins and minerals being the most commonly chosen options. A significant majority of participants 178(59.73%) reported changes in sleep patterns and weight-gain during the pandemic. The time spent watching TV and using computers, tablets and phones increased significantly during the isolation period (p<0.05). Also, there was a decrease in the physical activities of the academicians (p<0.05). Conclusion: Even within more aware segments of the population, such as academicians, the coronavirus disease-2019 pandemic’s impact on psychological wellbeing led to significant alterations in eating, sleeping and physical activity patterns. Key Words: COVID-19, Physical activity, Sleep, Feeding behaviour, Nutrition.